2010
DOI: 10.1186/1471-2377-10-37
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral toxoplasmosis in Acquired Immunodeficiency Syndrome (AIDS) patients also provides unifying pathophysiologic hypotheses for Holmes tremor

Abstract: BackgroundHolmes tremor is a rare symptomatic movement disorder. Currently suggested pathophysiological mechanisms of the disease are mostly derived from stroke cases. Although rare, cerebral toxoplasmosis may strengthen the pathophysiologic mechanism of disease.Case presentationA case of Holmes tremor secondary to cerebral toxoplasmosis in an AIDS patient is presented. A relevant literature search was performed, using pubmed and several entries for Holmes tremor as labelled in the literature. The unifying fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…7 The authors concluded that the dopaminergic deficit on DaTSCAN SPECT could be a predictor of levodopa responsiveness. 7 In another report, 3 the authors mentioned that all their patients improved to varying degrees with levodopa therapy, and they found that 18 F-dopa uptake showed values that were markedly and significantly decreased on the lesion side when compared to healthy controls and the contralateral side. However, some values were lower than those observed in parkinsonian patients.…”
Section: Opportunistic Infection In Aidsmentioning
confidence: 99%
“…7 The authors concluded that the dopaminergic deficit on DaTSCAN SPECT could be a predictor of levodopa responsiveness. 7 In another report, 3 the authors mentioned that all their patients improved to varying degrees with levodopa therapy, and they found that 18 F-dopa uptake showed values that were markedly and significantly decreased on the lesion side when compared to healthy controls and the contralateral side. However, some values were lower than those observed in parkinsonian patients.…”
Section: Opportunistic Infection In Aidsmentioning
confidence: 99%
“…The latency from lesion to tremor onset is usually about two months and its generation likely relies on a combined involvement of both the dopaminergic nigrostriatal system and the cerebello-thalamo-cortical pathways; however, pathophysiologic heterogeneity may account for a variable delay, as supported by DaTSCAN SPECT studies as well as by different therapeutic responses to levodopa, with only mild to moderate improvement ( Gajos et al, 2010 , Raina et al, 2016 ). Delayed tremor onset may also suggest a secondary neural degeneration along the dentate-rubro-olivary pathways ( Lekoubou et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of cases it is secondary to Toxoplasma abscesses in the mesencephalon of thalamus 27. Holmes tremor usually is a late feature.…”
Section: Headache and Tremor In Infectious Diseasementioning
confidence: 99%
“… 26 In the majority of cases it is secondary to Toxoplasma abscesses in the mesencephalon of thalamus. 27 Holmes tremor usually is a late feature. Lekoubou et al 27 describe a patient with a relatively short latency between onset of neurological signs and Holmes tremor, and even in this patient the tremor did not become apparent until 8 days after he first came to medical attention.…”
Section: Headache and Tremor In Infectious Diseasementioning
confidence: 99%